The Role Of Sub-Districts In Running The Program Village Infrastructure Facilities (PSPK) As Form Of Public Service Delivery: Research Study in Bengkong District – Batam City - Firdaus Firdaus; Fadlan Fadlan; Sayid Fadhil; Soerya Respationo; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The purpose of this writing is to discuss the issue of Legal Regulation and achievements and obstacles in the implementation of the Village Infrastructure Program (PSPK) as a form of public service implementation in Bengkong District. This is due to the overlap of regulations in the implementation of the Village Infrastructure Program activities, so it is necessary to know how the implementation of Batam City Regional Regulation Number 6 of 2021 concerning Community Empowerment-Based Development in Urban Villages and Batam Mayor Regulation Number 46 of 2022 concerning Guidelines for the Implementation of Facilities and Infrastructure Development Activities and Community Empowerment. To answer this problem, the author uses a methodology through a normative-empirical law research approach (applied law research), with data collection methods through observation and questionnaires Using a normative-empirical legal case study in the form of a legal behavior product, the subject of the study is the implementation or implementation of positive legal provisions, the results of this study show that the implementation of the Village Infrastructure Program (PSPK) in Bengkong District has not been implemented optimally, as well as many factors that hinder the implementation process, such as the lack of coordination between vertical agencies, resulting in overlapping regulations in its implementation. The implications are a). So that the Bengkong District Government re-socializes the Village Infrastructure Program (PSPK) to the community b). In order for the sub-district government to further improve coordination with vertical agencies regarding the implementation of Village Infrastructure Program (PSPK) activities. c). For the Bengkong District Government to make a proposal for an agreement with vertical agencies in proposing development through one sub-district door so that there is no overlap of rugals and budget waste.